ASPEK DRAMATIK LAKON KRESNA DUTA SAJIAN NARTASABDA - Mardjono Mardjono (Institut Seni Indonesia Surakarta, 2010)
Puppet world, especially Lakon Kresna Duta, has two main suppression, characterization and symbolization of Kurawa Pandawa, which can be a reflect on our lives. Kurawa is reflecting antagonist (insolence) while Pandawa is reflecting protagonist (goodness). In personality we can find not only badness and goodness but also variety. We can take the wisdom from the vary character in our lives. Problem of this paper is why Duryudana denies the King’s utterance and what tendency is behind his decision. Based on the problems, this paper aims to search and describe dramatic aspects that is theme, messages conveyed by the dalang, braided of events, the appeared controversy or conflict and the role of key character in the lakon. To reach the purpose, the writer uses approaches from performing arts, especially puppetry, and humaniora as well as social science. The result of the dramatic analysis is that Pandawa’s deeds in Lakon Kresna Duta is aimed to uphold the justice and truth in order to realize prosperity and it is not based on their ambitions. The wisdom that can be found is that it is very important for a leader to be honest, wise, and berbudi bawa leksana. A leader who propose virtue, berbudi bawa leksana will produce togetherness and tranquility, on the contrary, a leader who ignores virtue and always breaks his promise will lead to dispute and unpeacefulness which finally lead to destruction. Key words : shadow puppet, social, dramatic, lakon